Seasonal Variation and Frequency Distribution of Ectoparasites in Crossbreed Cattle in Southeastern Brazil. (8th October 2014) - Ferraz da Costa, Maria do Socorro; Guimarães, Marcos Pezzi; Lima, Walter dos Santos; Ferraz da Costa, Ana Julia; Facury Filho, Elias Jorge; Araujo, Ricardo Nascimento
Abstract : The aims of this study were to evaluate the seasonal variation and frequency distribution of Rhipicephalus (Boophilus) microplus, Haematobia irritans, and Dermatobia hominis on crossbred heifers under field conditions in the northeast of Minas Gerais state, southeastern Brazil. From November 2007 to September 2009 (23 months), 40 heifers aged 16.6 ± 2.4 months were divided into groups A (1 / 4 Holstein × 3/4 Gir) and B (1 / 2 Holstein × 1 / 2 Gir) and had the monthly infestation estimated along with the climatic conditions. The mean maximum and minimum temperatures were 28.5 and 19°C, respectively. The ectoparasites were present on animals in all months of the year. The levels of ticks on the animals were low (3.0 ± 0.2 ticks/animal), with the highest density in midwinter. The temperature was the climatic factor that most influenced the tick levels. The population of H. irritans (13.9 ± 0.3 flies/animal) and D. hominis (1.5 ± 0.2 larvae/animal) on heifers was more influenced by rainfall and exhibited two population peaks during the year. 1 / 2 Holstein heifers harbored significantly more H. irritans and D. hominis than 1 / 4 Holstein heifers. The results are discussed considering the most appropriate periods to apply ectoparasiticides and the genetic make-up of the animals.